(untitled) (Journal of the College of Basic Education, 2022)
Building form in Iraqi orchestra music compositions. The research aims to detect building Figure in the compositions of orchestral music in the works of Iraqi authors for the full orchestra Musical compositions written for small groups such as quartet or distribution are excluded Music or forms that contained choir groups